2020
DOI: 10.1007/s00253-020-10691-z
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of a monoclonal antibody against the sialidase of Gardnerella vaginalis using a synthetic peptide in a MAP8 format

Abstract: Bacterial vaginosis is one of the most frequent vaginal infections. Its main etiological agent is Gardnerella vaginalis, which produces several virulence factors involved in vaginal infection and colonization, in particular, sialidase (SLD), a potential clinical biomarker that participates in immune response modulation and mucus degradation. The main objective of this work was the production and evaluation of a monoclonal antibody against G. vaginalis sialidase and its validation in immunoassays. For immunizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Existing quantitative approaches targeting SLD are based on the catalytic activity of this enzyme, , which can be affected by variation in temperature/pH or any process leading to denaturation upon sample collection . Conversely, nanoBV does not measure the catalytic activity of SLD but the enzyme directly, even in denatured conditionsprovided the corresponding binding sites can still be recognized by the developed mAb . We hypothesize that this is the origin of the SLD levels reported by nanoBV, which are not in agreement with those SLD levels resulting from the aforementioned method based on enzymatic hydrolysis of methoxyphenyl acetyl muramic acid via SLD, since this method generally reports SLD levels lower than 600 ng mL –1 . , Consequently, our research also opens a debate on the SLD levels found in vaginal swab samples depending on the employed analytical platform.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Existing quantitative approaches targeting SLD are based on the catalytic activity of this enzyme, , which can be affected by variation in temperature/pH or any process leading to denaturation upon sample collection . Conversely, nanoBV does not measure the catalytic activity of SLD but the enzyme directly, even in denatured conditionsprovided the corresponding binding sites can still be recognized by the developed mAb . We hypothesize that this is the origin of the SLD levels reported by nanoBV, which are not in agreement with those SLD levels resulting from the aforementioned method based on enzymatic hydrolysis of methoxyphenyl acetyl muramic acid via SLD, since this method generally reports SLD levels lower than 600 ng mL –1 . , Consequently, our research also opens a debate on the SLD levels found in vaginal swab samples depending on the employed analytical platform.…”
Section: Resultsmentioning
confidence: 85%
“…We also compared the optimized LOD of nanoBV with that of an indirect enzyme-linked immunosorbent assay (ELISA) previously reported by our team, whose limit of detection accounted for 0.031 ng mL –1 (see Figure S6, SI); hence, nanoBV was observed to be 2.5-fold more sensitive than the indirect ELISA in terms of limit of detection. The overall cost of both detection platforms targeting SLD was also compared.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations